The Effect of Debt Policy on Firm Value with Profitability as a Moderating Variable: Evidence from PT Bank Rakyat Indonesia Tbk - Suci Rahmadani M; Trian Fisman Adisaputra; Abdul Hamid; Darwis (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2026)
This study aims to analyze the effect of debt policy on firm value with profitability as a moderating variable at PT Bank Rakyat Indonesia (Persero) Tbk. Although debt policy is a crucial component in the funding structure to maximize firm value, excessive use of debt risks creating financial burdens and liquidity disruptions, which often become gaps in a company's financial management strategy. Using a quantitative approach with secondary data sourced from annual financial reports published on the Indonesia Stock Exchange, this study applies a purposive sampling technique to select relevant data. The collected data are analyzed using Structural Equation Modeling (SEM) through SmartPLS software to test the relationship between variables. This study is expected to provide empirical evidence regarding the strategic role of profitability in moderating the relationship between debt policy and firm value. The results of this study contribute as a reference for company management in optimizing capital structure and assist investors in making more accurate investment decisions based on comprehensive financial performance indicators.